The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.21273/horttech03608-16
|View full text |Cite
|
Sign up to set email alerts
|

Using Technology to Enhance Extension Education and Outreach

Abstract: We held a technology session at the 2016 Annual Meeting of the American Society for Horticultural Science in Atlanta, GA, to provide guidance for technology choices in extension education and an opportunity to learn more about engaging new audiences, including the millennial generation (people born between 1982 and 2000). The use of technology is now an integral part of extension-client interaction. Presenters in the session gave examples of when technologies such as blogs, social media accounts, or we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…In contrast, the authors' Facebook followers are typically stakeholders or growers who are more likely to be seeking out new information. This is consistent with the findings in Barton et al (2017) where green industry consumers were more likely to be found on Facebook and professional conversations were more common on Twitter. In the future, the authors will use this information to better target program development efforts for CES clients on Facebook.…”
Section: Resultssupporting
confidence: 92%
“…In contrast, the authors' Facebook followers are typically stakeholders or growers who are more likely to be seeking out new information. This is consistent with the findings in Barton et al (2017) where green industry consumers were more likely to be found on Facebook and professional conversations were more common on Twitter. In the future, the authors will use this information to better target program development efforts for CES clients on Facebook.…”
Section: Resultssupporting
confidence: 92%
“…Social media platforms like YouTube are popular with younger generations; however, due to time constraints, the workshop focused on Instagram. The visually rich nature of horticultural subjects complements this image-based social media platform (Barton et al, 2017).…”
Section: Social Media Outreachmentioning
confidence: 99%
“…However, CH must do more than simply provide shareable content that is suitable for Instagram. In addition, CH must build its social media brand by actively engaging millennials by promptly answering posted questions, responding to comments, and asking for opinions and input (Barton et al, 2017). Millennial plant parents like to feel that they are partners with CH and that their opinions are heard, valued, and ''liked.''…”
Section: Social Media Outreachmentioning
confidence: 99%
See 1 more Smart Citation
“…But today, with the advancement in technology we have ample online extension methods like video conferencing, social networking applications, digital messages, etc. available for information dissemination (Barton et al, 2017;Capila & Sachdev, 2010). These methods contribute to a great extent not only in increasing knowledge of the people but also in meeting the developmental goals of communities (O'Donnell, 2009).…”
Section: Introductionmentioning
confidence: 99%